2014
DOI: 10.1186/1743-7075-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Herbal adaptogens combined with protein fractions from bovine colostrum and hen egg yolk reduce liver TNF-α expression and protein carbonylation in Western diet feeding in rats

Abstract: BackgroundWe examined if a purported anti-inflammatory supplement (AF) abrogated Western-diet (WD)-induced liver pathology in rats. AF contained: 1) protein concentrates from bovine colostrum and avian egg yolk; 2) herbal adaptogens and antioxidants; and 3) acetyl-L-carnitine.MethodsNine month-old male Brown Norway rats were allowed ad libitum access to WD for 41–43 days and randomly assigned to WD + AF feeding twice daily for the last 31–33 days (n = 8), or WD and water-placebo feeding twice daily for the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…Phenotypic changes in WD versus CTL rats are presented in Table 1 below. As reported previously [ 10 ], WD feeding significantly increased body mass at sacrifice by 6 % ( p = 0.0019), omental fat pad mass by 52 % ( p < 0.001), perirenal fat pad mass by 74 % ( p < 0.001), and liver fat deposition by 4.2-fold ( p = 0.004). We also previously reported that WD rats consumed 15 % more calories compared to CTL rats ( p < 0.001), with a diet higher in total fat, total sucrose, and total cholesterol.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Phenotypic changes in WD versus CTL rats are presented in Table 1 below. As reported previously [ 10 ], WD feeding significantly increased body mass at sacrifice by 6 % ( p = 0.0019), omental fat pad mass by 52 % ( p < 0.001), perirenal fat pad mass by 74 % ( p < 0.001), and liver fat deposition by 4.2-fold ( p = 0.004). We also previously reported that WD rats consumed 15 % more calories compared to CTL rats ( p < 0.001), with a diet higher in total fat, total sucrose, and total cholesterol.…”
Section: Resultssupporting
confidence: 85%
“… Values are means ± SE. Body mass, total kcal consumed, and Oil-Red O data previously reported [ 10 ]; symbols: g, grams; AUs, arbitrary units …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations